The internationalization of chinese companies : a case study on haier group. - Ng, Qi Hui. (2008)
In view of the fast pace at which the world is globalizing as well as the saturated global market, the Chinese, being a late entrant, finds it a struggle to gain a foothold in the global market and to catch up with established players. In this study, we hope to understand some of the problems the Chinese faced as a late entrant to the global market as well as the strategies that they can use to help themselves play the game of “catching up”.